Characterization of Mechanical and Damping Properties of Nettle and Glass Fiber Reinforced Hybrid Composites - Abbès, Fazilay; Xu, Shihua; Abbès, Boussad (Journal of Composites Science, 2022)
Growing environmental concerns are becoming significant challenges for large-scale applications in the automotive industry. Replacing and hybridizing glass fibers with natural fibers for non-structural applications is one effective way to address this challenge, while retaining the useful properties of both. This paper investigates the mechanical and damping performance of four types of compression-molded materials: polyester matrix (reference), nettle (6% by weight), hybrid 1 (6% glass and 6% nettle by weight), and hybrid 2 (12% glass and 6% nettle by weight), with polyester matrix at an ambient temperature. The tensile tests using digital image correlation (DIC) showed that by adding 6% by weight nettle fibers for polymer matrix tensile modulus increases by 21%. For the hybrid 1 two-layer composite (6% by weight glass and 6% by weight nettle) and the hybrid 2 three-layer composite (12% by weight glass and 6% by weight nettle), it increases by 80% and 101%, respectively. On the other hand, dynamic mechanical analysis (DMA) has been used to assess the damping properties of the materials. The results showed that the loss factor increased by 6~14% for nettle reinforced composite, by 8~25% for hybrid 1 glass-nettle reinforced composite and by 2~15% for hybrid 2 glass-nettle reinforced composite for frequencies around 1.0~2.0 Hz and around 12 Hz corresponding to vehicle body and suspension natural frequencies, respectively. These results showed that glass fibers can be replaced by nettle fibers without compromising performance.
Number: 8
Keywords: damping properties; dynamic mechanical analysis (DMA); hybrid composites; mechanical properties; nettle fiber